APPLYING TEXT-BASED APPROACH USING ECOTEXT TO IMPROVE DESCRIPTIVE WRITING SKILL OF THE 7TH GRADERS OF SMP KRISTEN PAYETI, EAST SUMBA - Dju Rohi, Melkyanus; Simpen, I Wayan; Sukarini, Ni Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 25 No 2 (2018): SeptemberDO - 10.24843/ling.2018.v25.i02.p08, 2018)
Text based approach is one of the approaches implemented in 2013 curriculum which is ignored by the English teacher in teaching. Besides, the teacher has not yet related the materials taught with the learners` environment, especially the local excellences.  This research aims to give a description both quantitatively and qualitatively on how the result of descriptive writing skill of the 7th graders’ of SMP Kristen Payeti before and after the implementation of text-based approach using ecotext with the theme of horse `njara` is. The data were collected through pretest, observation during the treatment, and posttest. This research uses concurrent embedded design in which the qualitative method is embedded or nested within the quantitative method. The results show that before the treatment the average achievement of the learners in composing descriptive text was 62. It is below the minimum completion criteria (KKM), that is 70. Individually, only 10 of 32 learners passed the exam. After the treatment, the average achievement became 78.69 or increased by 16.69 on five aspects analyzed, content, organization, vocabulary, language use, and mechanic. Only 3 of 32 learners failed. In addition, the treatment is suitable with the perspective of ecolinguistics in language learning, mainly the relation, the context, the emergence, the quality, the variability, and the activity. In conclusion, text based approach using ecotext can be implemented to improve the learners skill in writing descriptive text.